Cameroon : Staff Report for the Second Review Under the Poverty Reduction and Growth Facility Arrangement and Requests for a Waiver of Performance Criterion and for Additional Fund HIPC Interim Assistance. (IMF Staff Country Reports; Country Report ;, 2002)
This paper assesses Cameroon's Second Review Under the Poverty Reduction and Growth Facility (PRGF) Arrangement and a Request for a Waiver of Performance Criterion. Cameroon's good record of macroeconomic performance continued during the first annual program (October 2000-September 2001) under the new three-year PRGF arrangement. The structural reform process progressed further-albeit at a slow pace. Progress in implementing structural reforms slowed during the second half of the first annual program. The pace of economic activity was broadly in line with the envisaged real GDP growth of 5.3 percent.